Effects of carotid pressure waveforms on the results of wave separation, wave intensity and reservoir pressure analysis. (5th November 2018) - Di Lascio, N; Gemignani, V; Bianchini, E; Bruno, R M; Ghiadoni, L; Faita, F
Abstract: Objective : Recently great attention has been paid to innovative cardiovascular biomarkers obtained from wave separation (WS), wave intensity (WI) and reservoir-wave (RW) theories. All these approaches share a requirement for pressure information. The aim of this study was to evaluate differences in WS-, WI- and RW-derived parameters obtained achieving pressure waveforms in different ways. Approach : Twenty-two individuals (49  ±  17 years, 59% males) were examined. Common carotid blood flow waveforms were obtained from pulsed-wave Doppler images. Carotid pressure waveforms were achieved in four different ways: (1) with applanation tonometry, used as a reference method; (2) linear scaling from an ultrasound (US)-derived diameter curve; (3) exponential scaling from a US-derived diameter curve; and (4) linear scaling from an accelerometric-derived diameter signal. For each case, the reflection magnitude (RM) and index (RI) were obtained from the WS. The amplitude of the first positive peak ( W 1 ), of the second positive peak ( W 2 ) and of the negative peak ( W b ) were calculated from the WI, while the maximum of the reservoir (maxPr ) and the excess (maxPex ) pressure were achieved from the RW. Main results : According to the intra-class coefficient values, the agreement between the standard method and all the others was excellent for the RM (linear: 0.82; exponential: 0.83; accelerometric: 0.86), RI (linear: 0.84; exponential: 0.85; accelerometric: 0.87), maxPr (linear: 0.97; exponential: 0.96; accelerometric: 0.97) and maxPex (linear: 0.85; exponential: 0.87; accelerometric: 0.89), while only a fair/good level was reached for W 1 (linear: 0.67; exponential: 0.77; accelerometric: 0.52), W 2 (linear: 0.52; exponential: 0.69; accelerometric: 0.83) and W b (linear: 0.60; exponential: 0.44; accelerometric: 0.50). Significance : Measuring carotid pressure waveforms with different approaches does not influence the cardiovascular parameters obtained by WS and RW; those derived by WI are affected by the carotid pressure curve employed.